Medical Tourism: Patient’s Perspective: An analysis of patient satisfaction and perspectives in medical tourism (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In present scenario, every tourist going under medical treatment seeks better medical facility. Medical tourism is related with travelling overseas or other destinations for having different motives of treatment like surgeries, spas, and other health related activities. This type of tourism is preferred by patients who demand quality services, facilities, better doctors, less cost of their procedures and may be interested to receive medical care in places where they would like to spend their holidays. This review was conducted to find out patient’s satisfaction level while getting or after treatment and to assess the patients’ perspective regarding medical tourism. For attaining the above objectives, a review of published work such as articles, media sources and various reports concerning issues was consulted.